2016
DOI: 10.1177/0044118x16637883
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Matter With Civil Society? The Declining Effect of Civic Involvement on Civic Identity Among Czech Adolescents

Abstract: This study shows that the beneficial impact of adolescents' involvement in civil society on their civic identity cannot be taken for granted. Employing the case of the Czech Republic, it is shown that this effect has vanished since early post-communism to the present day. Survey data from two different generations of Czech middle adolescents were analyzed: the postcommunist generation (collected in 1995; n=1,127) and the current generation (collected in 2010; n=976). While participants' associational involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, extant research on CI relies predominantly on a qualitative approach and concentrates on highly engaged youth (e.g., Johnson, 2017). Regarding specific influences on CI development, various authors bring in the importance of civic knowledge (see Rubin, 2007 for a review), civic values, leadership experience (Lott, 2013), volunteering (Šerek, 2017), engagement in discussions and civic activities (Johnson, 2015). These findings offer a valuable insight into the potential developmental trajectories of CI by guiding research and policy planning, but the viability of generalizing to the population is low.…”
Section: Civic Identity and Its Developmentmentioning
confidence: 99%
“…Furthermore, extant research on CI relies predominantly on a qualitative approach and concentrates on highly engaged youth (e.g., Johnson, 2017). Regarding specific influences on CI development, various authors bring in the importance of civic knowledge (see Rubin, 2007 for a review), civic values, leadership experience (Lott, 2013), volunteering (Šerek, 2017), engagement in discussions and civic activities (Johnson, 2015). These findings offer a valuable insight into the potential developmental trajectories of CI by guiding research and policy planning, but the viability of generalizing to the population is low.…”
Section: Civic Identity and Its Developmentmentioning
confidence: 99%
“…Nonetheless, there is emerging evidence that participation in service does not necessarily lead to the development in civic identity (Mann & Casebeer, 2016). When adolescents are engaged in social organizations with a strong professionalization culture, the individual development of civic identity may not be supported (Serek, 2016). Empirical research that adopted Marcia's identity status model reported that an individual's participation in service activities had a negative relationship with identity diffusion but a positive association with identity achievement (Hardy, Pratt, Pancer, Olsen, & Lawford, 2011).…”
Section: Civic Identitymentioning
confidence: 99%